Clinical trials and trial-like studies on the use of traditional Chinese medicine to treat endometriosis. (September 2010) - Guo, Sun-Wei; He, Weiwei; Zhao, Ting; Liu, Xishi; Zhang, Tingting
There is a pressing need for the development of new therapeutics for endometriosis, and traditional Chinese medicine (TCM) is likely to be a treasure trove that will help to achieve this aim. We retrieved 851 papers on clinical studies evaluating the use of TCM to treat endometriosis that were published in the last 16 years and evaluated 153 of them that met our inclusion criteria. We found that the quality of these studies is well below an acceptable level, making it difficult to judge whether TCM is truly efficacious. There are signs that these studies, as a whole, have serious anomalies. The most glaringly deficient areas are informed consent, bias in evaluating outcome measures, follow-up, diagnosis, data analysis, report of adverse events and randomization. The uniformly low quality is alarming, given the large quantity of these studies, the enormous resources and energy put into these studies and, above all, the weighty issue of treatment efficacy that concerns each and every patient with endometriosis. Unless there is a dramatic change in attitude and practice, and perhaps an overhaul in education of research methodology, the efficacy and safety of TCM in treating endometriosis would remain questionable, which may force TCM into oblivion.